Population dynamics of Saissetia oleae. Ι. Assessments of ροpulation and mortality - Stratopoulou, E. T.; Kapatos, Ε.Τ. (ENTOMOLOGIA HELLENICA, 1990)
The population dynamics of Saisselia oleae (Oliv.) (Homoptera: Coccidae) was studied in Corfu during five successive yearly generations (1981-1986). Successive estimates of the population of S. oleae were obtained within each of the five yearly generations and survivorship curves were constructed showing the progressive reduction of the living population within each generation and population changes from generation to generation. The calculated mortality rates indicate that the population of S. oleae suffers heavy mortality. The major mortality factors were high temperatures during summer, the action of predators, particularly during spring, and mortality of crawlers during summer. Overall survival rate was very low and corresponded to total generation mortality that ranged from 99.693% to 99.987%. It is assumed that variation in the action of mortality factors cause considerable I’l Uctuations of the S. oleae population.